1999
DOI: 10.1002/(sici)1521-3951(199906)213:2<433::aid-pssb433>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

NMR Studies of Mixed Y3?xYbxAl5O12 Crystals

Abstract: 27Al NMR studies of the Y3—xYbxAl5O12 mixed garnets were performed. The magnetic moment of Yb3+ ions in the garnets was determined. The quadrupole coupling constants were calculated for Al in a‐ and d‐positions. It was shown that the mixed garnets with x = 0.75 and 1.00 should be treated as partially ordered solid solutions. A model of substitutional ordering for these mixed garnets was suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Only the mean magnetic moment of the paramagnetic Yb 3+ cations was considered in the analysis, but again useful information about cation distributions were obtained. 40 An early single-crystal 27 Al NMR study of a very iron-rich natural garnet reported a similar phenomenon. 39 In a high-resolution NMR study of powders of Tb 3+ -containing Y 3 Al 5 O 12 , additional 89 Y MAS NMR peaks appeared at higher dopant concentrations and were attributed to pseudo-contact interactions, while resonances for both this nuclide and 27 Al were severely broadened at high Tb contents.…”
Section: Signal Loss and Peak Shiftsmentioning
confidence: 77%
See 2 more Smart Citations
“…Only the mean magnetic moment of the paramagnetic Yb 3+ cations was considered in the analysis, but again useful information about cation distributions were obtained. 40 An early single-crystal 27 Al NMR study of a very iron-rich natural garnet reported a similar phenomenon. 39 In a high-resolution NMR study of powders of Tb 3+ -containing Y 3 Al 5 O 12 , additional 89 Y MAS NMR peaks appeared at higher dopant concentrations and were attributed to pseudo-contact interactions, while resonances for both this nuclide and 27 Al were severely broadened at high Tb contents.…”
Section: Signal Loss and Peak Shiftsmentioning
confidence: 77%
“…For single crystals of mixed Y 3Àx Yb x Al 5 O 12 (''YAG'') garnet, large electron-nuclear dipolar shifts in 27 Al resonances were observed as a function of crystal orientation in the external field. 40 Most or all of such shifts would be averaged by MAS or by tumbling in a liquid, leaving only a residual contribution or pseudocontact effect if the magnetic susceptibility at the paramagnetic site is anisotropic. Only the mean magnetic moment of the paramagnetic Yb 3+ cations was considered in the analysis, but again useful information about cation distributions were obtained.…”
Section: Signal Loss and Peak Shiftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since nuclear magnetic resonance (NMR) characteristics such as chemical shift, line shape, and relaxation times are very sensitive to the local structure in crystals, NMR investigation should be quite fruitful for revealing the substitutional order in mixed crystals, especially in the case of weak ordering. In fact, NMR has been used to study the partial substitutional order in the Y 3−x Yb x Al 5 O 12 mixed garnets [9], in mixed yttrium-erbium aluminates [10], and in binary and ternary semiconductor solid solutions (see [5,11,12] and references therein). In [9,10], the 27 Al absorption line shape was analysed; various numbers of paramagnetic Yb and Er ions in the Al surroundings were detected due to large shifts induced by interaction with electron moments.…”
Section: Introductionmentioning
confidence: 99%
“…For static (nonspinning) single crystals (or powders), the effects of paramagnetic cations are most likely dominated by large through-space dipolar couplings, which have long been measured to provide information on site occupancies. For example, in the 1 H and 19 F spectra of micas, the intensities of small dipolar-shifted resonances provided unique constraints on nonrandom association of Fe 2+ with OH À versus F À anions (Sanz & Stone, 1979); numerous 27 Al NMR studies of single crystals of yttrium aluminum garnet (YAG) laser materials with various paramagnetic (and optically active) rare earth dopants have indicated that random dodecahedral site mixing prevails (Charnaya et al, 1999;Vorob'ev et al, 1998), following an early report on an FeO-rich natural silicate garnet (Ghose, 1964). More modern approaches to high-resolution paramagnetic NMR, particularly in biomolecular solids, have been recently reviewed (Pintacuda & Kervern, 2013).…”
Section: Paramagnetic Shifts: Background and Practical Considerationsmentioning
confidence: 99%